PENGEMBANGAN DAN VALIDASI KUESIONER DAMPAK EVENT OLAHRAGA PADA MASYARAKAT (KDEOPM) - Miftah Fariz Prima Putra; Tri Setyo Guntoro (Fakultas Seni Rupa dan Desain ITB, 2021)
The purpose of this study was to develop an instrument that reveals public perception related to the impact of organizingsports events. Theoretically, four aspects were used as an indicator in understanding the impact of sports events onsociety, namely economic, psycho-social, infrastructure, and environmental aspects. The four aspects were broken downinto 46 statements with five alternative answers. The validation test involved 113 respondents, consisting of 77 (68.14%)male, 36 (31.86%) women. The age range was between 17 - 70 years (M = 32.6 ± 10.9) and the level of educationwas from elementary school to Doctoral degree (S3) with a wide variety of occupational backgrounds. The results ofexplanatory factor analysis found the variables of sports events can be explained by four factors (economic, psychosocial, infrastructure, and environment) with a value of 63.24% (approximately 10.37% for the first factor, 13.096%for the second factor, 7.94% for the third factor and 6.43% for the fourth factor). A correlation coefficient test betweenfactors, totals, and items-total found environmental factors to have low coefficient values (r = -0.005, Sig. 0.961), andthree items in that factor had a value of < 0.3. Hence, environmental factors and items were excluded from the instrument. The results found that there were 26 items declared valid and reliable with validity values of 0.462 - 0.744 and reliability of 0.881 - 0.934. Thus, the property of the instrument developed was declared valid and reliable in revealing public perception of the impact of sports events.